EFEKTIVITAS PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI SMP PAB 7 MANUNGGAL - Syafrida Hanum Hutasuhut (MES: Journal of Mathematics Education and Science, 2023)
In the process of learning mathematics, students are not only required to understand concepts, but more than that. One of the important skills mastered by students is mathematical communication skills. The purpose of this research is to see the effectiveness of problem-based learning in improving students' communication skills. This study aims to provide an overview of the quality of the research variables studied. The variables in this study consisted of two, namely the application of problem-based learning and the mathematical communication skills of students of SMP PAB 7 Manunggal. As for the subject of this study is the application of problem-based learning models and the object of this study is students' mathematical communication skills. The sample in this study were 28 grade VII students of SMP PAB 7 Manunggal. The instruments used to collect research data were questionnaires to observe the implementation of the learning process and test sheets for mathematical communication skills that had been tested for their validation and reliability levels. The data collected in this study were then analyzed to see the effectiveness of the implementation of the learning process and students' mathematical communication skills. Problem-based learning implemented at SMP PAB 7 Manunggal can be said to have been effective in terms of the implementation of the learning process with an average score of observations of 3.589 and student learning completeness reaching 75%. Because the learning process implemented has been said to be effective, data on students' mathematical communication abilities can be analyzed to see the improvement. Based on the descriptive comparison of the test result data, it can be concluded that there has been an increase in students' mathematical communication abilities, in terms of pre-test and post-test scores.